HAK SEWA SEBAGAI HARTA BENDA WAKAF PERSPEKTIF HUKUM ISLAM - Hilman, Nur Insyirah; Patimah; Musyfikah Ilyas (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
The development of waqf at this time was very rapid and varied, both the waqf property for good and for a certain period of time. This study aims to determine the existence and views of Islamic law on rental rights as waqf property and the implementation of RI Law no. 41 of 2004 concerning waqf. This research is library research in which the collection of information and data is obtained from various literatures, theses and related books. The results of this study indicate that the existence of lease rights as waqf property in order to obtain benefits from the waqf property. The enactment of the waqf law is expected to make the public more aware of waqf and professional management to produce something more tangible. Islamic law allows rental rights as waqf property because there are no legal provisions that explicitly prohibit it and the development of waqf comes from the results of ijtihad. Reviewing the public's understanding of waqf, which may have been a mistake in understanding the implementation of waqf due to the lack of evidence that discusses waqf. Therefore, it is necessary to socialize about waqf both regarding waqf property, the purpose and function of waqf itself by looking at the social conditions of the community.